Alat Pemilah Sampah Otomatis Kategori Logam, Plastik dan Kertas Menggunakan Arduino Uno - Aldi Aldi; Ayu Mawadda Warohma (MDP Student Conference, 2026)
The issue of waste remains a challenge due to the suboptimal sorting of waste at source, which results in the sorting process still being largely manual and inefficient. This study aims to design and implement an automatic waste sorting device capable of classifying metal, plastic, and paper waste using an Arduino Uno microcontroller. This system integrates an infrared sensor to detect the presence of waste, a capacitive proximity sensor as an initial detector, and an inductive proximity sensor for selective identification of metal waste. A servo motor is used to direct waste to the appropriate compartment, while an ultrasonic sensor monitors the capacity of the waste bin. Testing was conducted using 30 waste samples, with the system achieving an accuracy rate of 90%. These results indicate that the device operates reliably and effectively in performing automatic waste sorting.